Game over: Empirical support for soccer bets regulation - Emanuel Vahid Towfigh; Andreas Glöckner (Max Planck Institute for Research on Collective Goods, 2010)
In many countries, betting in sports is highly regulated. In Germany, however, there are current debates whether regulation should be loosened. A crucial part of the argument is that sport bets could be qualified as games of skill that are considered to be less dangerous by German Law than games of chance and are thus assumed to need less regulation. We explore this hypothesis in three incentivized online studies on soccer betting (N=214) and provide evidence against two crucial parts of this argument. First, we show that there are no overall effects of skill on accuracy in soccer bets and monetary earnings do not increase with skill. Hence, soccer betting cannot be considered a game of skill. Second, we show that soccer betting induces strong overconfidence and illusion of control, particularly for people who assume they have high skill, and that these biases lead to increased betting. Cognitive biases that might cause financial harm for bettors or even lead to problematic or pathological gambling behavior are even stronger for soccer bets compared to bets on the outcome of lotteries. Concerning the main aims of legal regulation for gambling in German law, our results strongly speak for regulation of soccer bets.
Keywords: 330; Expertise; Betting; Judgments; Overconfidence; Illusion of Control; Glücksspiel; Sport; Regulierung; Konsumentenverhalten; Sachverständige; Deutschland